A new species and a new form of leafhopper from the Great Smoky Mountains National Park (Hemiptera: Cicadellidae: Typhlocybinae) - Dmitriev, Dmitry A.; Zahniser, James N. (Zootaxa, 2017)
A new species Erasmoneura tricuspidata sp.n. and a new morphological variant of Erythridula stolata McAtee are described from the Great Smoky Mountains National Park.